EDEM Simulation of Particles Path in a Vertical Cyclone Separator - Zulkifli, Mohammad Zulkhairi (2022)
Systematically investigating the relationship between cyclone separator particle trajectory, as well as the impact different particle loadings on cyclone separator wall due to contact from particle collision is investigated in this paper.